Gender Egalitarianism as a Value of International Labor Relations - Khamzina, Zhanna; Yermukhametova, Saulegul; Turlykhankyzy, Kuralay; Yessengazieva, Ainur; Oryntayev, Zhambyl; Buribayev, Yermek (Տիգրան Մեծ)
Gender philosophy, issues of gender identity and gender inequality are topical issues of the philosophical and legal scientific direction. The manuscript presents an approach that includes understanding gender issues in labor relations from the standpoint of the social state, relations of equality, justice and the common good. Only by gaining a foothold in theory and practice, constantly rising to the level of its philosophical generalization, the ideas of gender equality provide a mechanism for their real implementation, and the gender approach serves to effectively solve problems and preserve social peace. The principle of gender equality acts as a goal that must be taken into account in lawmaking and law enforcement. The purpose of the study is to determine the place and role of international legal instruments in the formation of national methods for ensuring gender equality and processes related to the improvement of mechanisms for protection against discrimination. The study is based on the assumption that international labor agreements have the necessary leverage over national legal systems and that it is in the public interest to effectively implement and enforce them.
Keywords: International law